Aspectos morfológicos da ação de reguladores do crescimento em estacas de Araucaria angustifolia (Bert) O. Ktze. - Iritani, Cecília; Soares, Ronaldo Viana; Gomes, Aracely V. (Acta Biológica Paranaense, 1986)
Aspectos morfológicos da ação de reguladores do crescimento em estacas de Araucaria angustifolia (Bert) O. Ktze.